MacroD1 sustains mitochondrial integrity and oxidative metabolism - Ann-Katrin Hopp; Lorenza P. Ferretti; Lisa Schlicker; Amalia Ruiz-Serrano; Udo Hetzel; Francesco Prisco; Anja Kipar; Lukas Muskalla; Elena Ferrari; Carsten C. Scholz; Karsten Hiller; Francisco Verdeguer; et al. (Nature Communications)
Abstract The mono-ADP-ribosylhydrolase MacroD1 has been recently reported to localize to mitochondria exclusively. However, the extent and means by which MacroD1 regulates metabolic homeostasis remains unclear. Here we show that the absence of MacroD1 in mice decreased mitochondrial load and negatively impacted muscle function, reducing maximal exercise capacity. Knockdown of MacroD1 in C2C12 myoblast cells amplified the production of reactive oxygen species which ultimately resulted in increased mitochondrial fission. Proteomic and metabolomic profiling showed that loss of MacroD1 re-routed metabolite flux from glucose to the pentose-phosphate cycle instead of the tricarboxylic acid cycle to support the production of antioxidants, including glutathione and NADPH. This resulted in increased glucose uptake and dependency both in vitro and in vivo. Hence, our research establishes MacroD1 as a regulator of metabolic homeostasis, which ensures the coordination of cellular carbohydrate flux and optimal mitochondrial function.